Study of the effectiveness of applying a double dose of ginger root extract for the treatment of osteoarthritis of the knee joints and hands - V.M. Kovalenko; A.S. Krylova (Bolʹ, Sustavy, Pozvonočnik, 2025)
Background. Osteoarthritis is the most common form of arthritis and the main cause of disability. One of the promising drugs is ginger root extract, since there is a new data on its analgetic and anti-inflammatory properties. The aim of the study was to test effectiveness and safety of a double dose of ginger root extract treatment in patients with knee and hands osteoarthritis. Materials and methods. The study included 58 patients (11 men and 47 women) with osteoarthritis, aged 30 to 80 years, 32 patients had knee osteoarthritis and 26 patients — hand osteoarthritis. Patients were orally administered 1200 mg per day commercially available ginger extract for 6 months. Methods: general clinical, questionnaires (filling in adapted questionnaires), laboratory (cholesterol, blood glucose, bilirubin, ALT, AST, creatinine in the blood), instrumental studies (X-ray examination of joints, ultrasound examination of joints), methods of biomedical statistics. Results. Ginger root extract treatment resulted in a statistically significant decrease in the severity of pain according to visual analogue scale (VAS) by 60 % (p < 0.05), a statistically significant (p < 0.05) decrease in the number of attacks of knee osteoarthritis, the duration of attacks in days and the number of days NSAIDs intake. Beneficial effects of a double dose of ginger root extract are a statistically significant (p < 0.05) decrease in the intensity of the pain syndrome according to VAS by 33 %, the FIHOA index by 28 % and the AUSCAN pain, functional activity indices, a decrease in the total synovitis score and Doppler activity by ultrasound of the hand joints for the distal and proximal interphalangeal joints of the II–IV fingers. The tolerability of 1200 mg of ginger root extract per day was confirmed by reflux (RSI) and dyspepsia (SODA) questionnaires. Conclusion. Based on our study, it can be assumed that an increased dose of ginger root extract (1200 mg per day) may be effective and safe for the treatment knee and hand osteoarthritis.